Dynamic Relationship Analysis between Foreign Direct Investment, Exports, Imports, and Economic Growth in Afghanistan: An ARDL Model Approach - Mohammadi, Karimullah; Faqiri, Mohammad Mahfoz (Journal of Social Sciences and Humanities, 2026)
The purpose of this study is to examine the interrelationship among foreign direct investment (FDI), exports, imports, and economic growth in Afghanistan during the period 2002–2023. To achieve this objective, annual time series data and the Autoregressive Distributed Lag (ARDL) econometric model were employed. The estimation results indicate that the negative and statistically significant coefficient of the error correction term (-0.2694) reflects an adjustment speed of approximately 27 percent of short-term deviations in gross domestic product (GDP) toward long-term equilibrium in each period, confirming the existence of a cointegrating relationship among the variables. In the short run, exports exert a negative and significant effect on economic growth, whereas imports demonstrate a positive and significant influence. In the long run, FDI with a positive and significant coefficient (0.1775) and imports with a positive and significant coefficient (0.012137) play a crucial role in enhancing economic growth, while exports show no significant effect. A comparison of these findings with previous studies reveals both similarities and differences, largely attributable to Afghanistan’s institutional, structural, and security conditions. The results highlight that targeted attraction of foreign direct investment, facilitation of capital goods imports, and structural reforms in the export sector can contribute to sustainable economic growth in Afghanistan.